(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This study is devoted to analysing the deep interrelationships between Oriental poetry and Uzbek literature. The paper examines how the rich traditions and stylistic techniques of oriental poets have had a significant influence on the formation and development of Uzbek poetry. Particular attention is paid to the influence of such genres as the ghazal, kasida, and rubai on Uzbek poetry of various historical periods. The paper examines how the traditions of oriental poetry continue to influence contemporary Uzbek poetry. It analyses the works of contemporary poets, in which echoes of classical examples can be detected.